2012
DOI: 10.1152/ajpendo.00035.2011
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib induces apoptosis in pheochromocytoma tumor cells by inhibiting VEGFR2/Akt/mTOR/S6K1 pathways through modulation of Bcl-2 and BAD

Abstract: Sunitinib is an oral multitargeted receptor tyrosine kinase inhibitor with antiangiogenic and antitumor activity that mainly targets vascular endothelial growth factor receptors (VEGFRs). Very recently, sunitinib has been shown to be an active agent for the treatment of malignant pheochromocytomas. However, it is unclear whether sunitinib acts only through an antiangiogenic mechanism or whether it may also directly target tumor cells. Sunitinib markedly induced apoptosis of PC12 cells in a dose-dependent and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 47 publications
(62 reference statements)
7
38
0
Order By: Relevance
“…These facts suggest that VEGF did not affect PC12 cell growth directly, but indirectly contributed to the growth of xenografted PC12 tumour in vivo by stimulation of angiogenesis. These observations can also explain the fact that in our experiments endostatin, which acts mainly by blocking VEGF/VEGFR signalling [38], does not have any effect on the growth of PC12 cell line. Moreover, other authors did not show a direct binding of endostatin to the PC12 cell surface [28,39], suggesting the absence of receptors for endostatin in this cell line.…”
Section: Prace Oryginalnesupporting
confidence: 62%
“…These facts suggest that VEGF did not affect PC12 cell growth directly, but indirectly contributed to the growth of xenografted PC12 tumour in vivo by stimulation of angiogenesis. These observations can also explain the fact that in our experiments endostatin, which acts mainly by blocking VEGF/VEGFR signalling [38], does not have any effect on the growth of PC12 cell line. Moreover, other authors did not show a direct binding of endostatin to the PC12 cell surface [28,39], suggesting the absence of receptors for endostatin in this cell line.…”
Section: Prace Oryginalnesupporting
confidence: 62%
“…Very recently, sunitinib was proven to be an active agent in the treatment of malignant pheochromocytomas (3 -5). Previously, we demonstrated that sunitinib directly inhibited mTORC1 signaling, which in turn led to apoptosis in PC12 cells (6). This indicated that sunitinib may exert its antitumor effects, at least in part, directly via tumor cells rather than by antiangiogenesis.…”
Section: Introductionmentioning
confidence: 86%
“…Unlike RGZ-induced autophagy in adrenocortical carcinoma cells, however, current research suggests that chemically induced autophagy in the rat pheochromocytoma cell line, PC12, promotes cell survival (Ikeda et al 2013, Fabrizi et al 2014. For example, sunitinib, a known anticancer drug, induces both apoptosis and autophagy in PC12 cells, most likely through the direct inhibition of mTOR (Saito et al 2012, Ikeda et al 2013. The inhibition of autophagy, however, increased the apoptotic and antiproliferative effects of sunitinib treatment in PC12 cells (Ikeda et al 2013), implying that in this case autophagy is acting against the anticancer effects of sunitinib and in favor of PC12 cell survival.…”
Section: Autophagy In Adrenal Cancermentioning
confidence: 99%
“…With only three studies on the topic, however, it is impossible to generalize the results to any useful effect. Furthermore, all of the studies were conducted in vitro on cell lines that, in the case of the rat PC12 cells, are known to imprecisely represent malignant pheochromocytoma cells (Saito et al 2012). Future research is required to elucidate the specifics of autophagy in the different types of adrenal cancer in vitro and in vivo and take full advantage of its therapeutic potential as a target for induction or inhibition, as indicated.…”
Section: Autophagy In Adrenal Cancermentioning
confidence: 99%